Develop a Communities of Practice Supported Training Process for English Teachers, Morejoy Education Training Center, Chongqing, China - Deng Meini (2019)
© 2018 IEEE. This research is based on the problem existed among all K12 training center in China, and also occurred in the case study of this research, Morejoy Education. Morejoy Education is the market post of small-scale K12 training center, Chongqing. The common existed problem among K12 training centers is teachers' teaching performance cannot be enhanced through already existing training model in the training center. Researcher used interview to find out the prevalent problem is happened in Morejoy also. Owing that teachers are the key factor of training center, teachers' teaching performance influence students' learning outcome and training center's reputation, which helps to attract resources of students. By virtue of teaching record and Communities of Practice, an appropriate teachers' training process for small-scale training center is built, which aims at helping zero-year experienced English teachers to improve their teaching performance and solving the common problem.